CYP52X1, representing new cytochrome P450 subfamily, displays fatty acid hydroxylase activity and contributes to virulence and growth on insect cuticular substrates in entomopathogenic fungus Beauveria bassiana - Zhang, Shizhu (2012)
Infection of insects by the entomopathogenic fungus Beauveria bassiana proceeds via attachment and penetration of the host cuticle. The outermost epicuticular layer or waxy layer of the insect represents a structure rich in lipids including abundant amounts of hydrocarbons and fatty acids. A member of a novel cytochrome P450 subfamily, CYP52X1, implicated in fatty acid assimilation by B. bassiana was characterized. B. bassiana targeted gene knockouts lacking Bbcyp52x1 displayed reduced virulence when topically applied to Galleria mellonella, but no reduction in virulence was noted when the insect cuticle was bypassed using an intrahemoceol injection assay. No significant growth defects were noted in the mutant as compared with the wild-type parent on any lipids substrates tested including alkanes and fatty acids. Insect epicuticle germination assays, however, showed reduced germination of ΔBbcyp52x1 conidia on grasshopper wings as compared with the wild-type parent. Complementation of the gene-knock with the full-length gene restored virulence and insect epicuticle germination to wild-type levels. Heterologous expression of CYP52X1 in yeast was used to characterize the substrate specificity of the enzyme. CYP52X1 displayed the highest activity against midrange fatty acids (C12:0 and C14:0) and epoxy stearic acid, 4-8-fold lower activity against C16:0, C18:1, and C18:2, and little to no activity against C9:0 and C18:0. Analyses of the products of the C12:0 and C18:1 reactions confirmed NADPH-dependent regioselective addition of a terminal hydroxyl to the substrates (ω-hydroxylase). These data implicate CYP52X1 as contributing to the penetration of the host cuticle via facilitating the assimilation of insect epicuticle lipids.